2017
DOI: 10.1111/fcp.12285
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin‐1b and its antagonist (diacerein) in estradiol benzoate‐induced endometrial hyperplasia and atypia in female rats

Abstract: Endometrial hyperplasia (EH) is a common gynecological condition and may progress to carcinoma. We investigated the effect of diacerein (DIA) on estradiol benzoate (EB)-induced EH and atypia. DIA (50 mg/kg/day) was administered orally to rats for 4 weeks, in the presence or absence of EH induced by intramuscular injection of EB (60 μg/100 g) three times per week for 4 weeks. We measured levels of serum total cholesterol, uterine tissue malondialdehyde (MDA), total nitrites (NO ), superoxide dismutase (SOD) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
12
20
0
1
Order By: Relevance
“…The major lipid peroxidation end product of the cardiomyocyte membrane is MDA. The high level of MDA indicates oxidative stress and decreased activity of antioxidant enzymes that results in irreversible cell damage; this is considered an important marker of cardiac injury .…”
Section: Discussionmentioning
confidence: 99%
“…The major lipid peroxidation end product of the cardiomyocyte membrane is MDA. The high level of MDA indicates oxidative stress and decreased activity of antioxidant enzymes that results in irreversible cell damage; this is considered an important marker of cardiac injury .…”
Section: Discussionmentioning
confidence: 99%
“…The effect is due to the ability of ZEA to bind to oestrogen receptors (ERs) (Vantomme, Swings, Goor, Kersters, & De, 2007). Estradiol benzoate (EB) is an estradiol (E 2 ) derivative, with similar effects to E 2 (Refaie & Elhussieny, 2017). Clinically, EB is commonly used to relieve symptoms such as post-partum haemorrhage after caesarean section (Sun, Ling, & Sun, 2001) and clinical symptoms of menopause in women (Sherwin, 2005a(Sherwin, ,2005b.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is not easily degraded, EB enters the food chain through the soil, water and air. It is also worth noting that exposure to a dose of oestrogen could lead to endometrial hyperplasia and sexual organ dysplasia (Degen & Bolt, 2000;Refaie & Elhussieny, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that diacerein increased hepatic GSH content but decreased MDA level. Coincided with that, Refaie and El-Hussieny [22] found that diacerein reduced uterine MDA level and increased SOD activity in estradiol benzoate-induced endometrial hyperplasia and atypia in rats with improvement of estradiol benzoate induced histopathological damages.…”
Section: Discussionmentioning
confidence: 69%